Pengaruh Variasi Girder Terhadap Perilaku Struktur Atas Jembatan Beton Prategang Akibat Gempa Horizontal - Septiano H.E. Tefa; Dantje A.T Sina; Andi Kumalawati (Universitas Nusa Cendana, 2022)
Earthquakes are dangerous natural disasters and cause damage on a large scale. Therefore, this study aimed to determine the mass participation of the structure, structure capacity, and performance levels. The analysis was carried out based on the spectral response, pushover, and FEMA-356 methods. In anticipation of the damage, the design of earthquake-resistant structures has become essential in structural design, especially in the bridge structure design. The bridge samples in this study were type I prestressed concrete bridges with a length of 37 m and a width of 4 m using ten variations of girders located at the Temef Dam. The results obtained are the most critical structural conditions occur in the transverse direction. The base shear maximum capacity is more significant in the longitudinal direction than in the transversal direction. The maximum displacement capacity is higher in the transversal direction than in the longitudinal direction. The effect of cross-sectional area and cross-sectional inertia of the beam girder on the structural’s capacity is the greater the cross-sectional area and inertia of the beam girder, the greater the capacity of the structures. All of The structure performance levels were Immediate Occupancy (IO).